1994
DOI: 10.1007/bf01379114
|View full text |Cite
|
Sign up to set email alerts
|

Mutual interactions between HIV-1 and cytokines in adherent cells during acute infection

Abstract: The production of cytokines by HIV-infected cells from adherent tissues as well as their effects on HIV replication in the same cells were investigated. CD4-transfected HeLa-T4-6c epithelial cells, CD4-positive normal lung fibroblasts and CD4-negative RD rhabdomyosarcoma cells were infected with HIV-1. All cultures were permissive for virus replication, which was completed within 48-72 h by Hela-T4-6c and RD cells and 2-3 weeks in normal fibroblasts. During the course of HIV replication, a series of cytokines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] As shown by an experiment on PEU cells in Fig. 1A and B), both strains replicated and were released.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] As shown by an experiment on PEU cells in Fig. 1A and B), both strains replicated and were released.…”
Section: Resultsmentioning
confidence: 96%
“…Our studies of HIV-infected human diploid fibroblasts indicate that virus replication is also stimulated by tumor necrosis factor a in these targets,5 and that HIV-inductive cytokines are produced in vitro by fibroblasts and other cells from solid tissues, in parallel to HIV replication.20 Thus inflammatory stimuli causing the local release of cytokines would enhance HIV production by stromal cells, hence accelerating virus transmission both within the organ and to infiltrating cells. 20 …”
Section: Discussionmentioning
confidence: 97%
“…Various human cell types were exposed to HIV-T and HIV-E (MOI of 2 pg/cell) for 1 hr at 0°C, to determine the extent of HIV binding, as described. 17,22 As shown in Fig. 1A, the amounts of HIV-T bound to C8166 cells, peripheral blood mononuclear cells (PBMCs), and monocyte-derived macrophages (MDMs) were higher compared with HIV-E, which, conversely, showed higher binding to PEU diploid fibroblasts 20 of different origin, such as colonic HT-29, mammary MEC-1, 8 renal MC mesangial, and proximal tubular epithelial cells, 23 and uroepithelial T-24 cells.…”
mentioning
confidence: 85%
“…B OTH ex vivo AND in vitro STUDIES showed that human immunodeficiency virus type 1 (HIV-1) infects epithelial cells from different body sites, such as the oral cavity, 1 gastrointestinal tract, 2-5 mammary glands, 6-8 adrenal glands, 9 salivary glands, 10 kidney, [11][12][13] liver, 14 thymus, 15 and eye. 16 Cells of the genital tract are infected in vitro, 2,10,17 but no ex vivo evidence of HIV replication has been found so far. 18,19 In epithelial cells and fibroblasts the replication rate is low, although significant, 8,12,20,21 and persistent infections can occur.…”
mentioning
confidence: 96%
See 1 more Smart Citation